Exposure to Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) inhibitors and the association with neurocognitive side effects: a meta-analysis and meta-regression. (25th November 2020) - Hirsh-Raccah, B; Yanovsky, A; Rotshild, V; Danenberg, H; Eliaz, R; Matok, I
Abstract: Background: Lipid lowering therapy may be associated with impaired cognitive function. The association between the use of Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) inhibitors and the risk of neurocognitive adverse effects remains unclear. Purpose: To assess the neurocognitive safety of PCSK9 inhibitors using meta-analysis and meta-regression of randomized controlled trials (RCTs). Methods: PubMed (MEDLINE), Embase and Cochrane library were searched. RCTs that reported assessments of neurocognitive outcomes of participants using PCSK9 inhibitors, with a duration of follow up of at least six months were included. The results of the search were screened by two independent reviewers. Any disagreements were resolved by consensus. The research was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension statement for meta-analyses. Results were pooled using random-effects models. The primary safety outcome of this analysis was defined as the reported incidence of neurocognitive adverse effects. Results: Results of 21 trials were included in the analysis. Among 59, 733 patients, 31, 611 were treated with PCSK9 inhibitors. No significant difference in the incidence of neurocognitive side effects between the treatment and control groups was identified (RR=1.01, 95% CI: 0.86–1.19, I2=3%). Same results were seen in separate analysis for each of the medicines (Alirocumab- RR=0.88, 95% CI: 0.72–1.08, I2=0%, Evolocumab- RR=1.42, 95% CI: 0.74–2.73, I2=55%). In a meta-regression analysis there was no statistically significant association between the assessed and the risk for neurocognitive side effects. Conclusions: Pooled results of our meta-analysis and meta-regression clearly show that the exposure to PCSK9 inhibitors is not associated with an increased risk of neurocognitive adverse events. Due to the increasing proportion of patients using lipid-lowering therapy these results are positively reassuring. However, more data from long-term outcomes studies is needed to further evaluate the effect of longer exposure to PCSK9 inhibitors Funding Acknowledgement: Type of funding source: None